On the Status of the 2nd Person Singular Marker -s - Karlík, Petr (Bohemica Olomucensia, 2024)
The study tries to show how the schizophrenic behavior of the Czech phi-marker -s both as a C-2 clitic (Ty-s četl // Ty jsi četl "You've read") and a V-clitic (Ty četl-s // *Ty četl jsi "You've read") could be derived within the theoretical framework of the phi-feature geometric analysis.
Keywords: clitics; phi-feature inflection; feature geometry; unique phi-feature marker in Czech